An analysis of longitudinal and transverse arches of children from świętokrzyskie voivodship - Beata Szczepanowska-Wołowiec; Paulina Sztandera; Jakub Zbyradowski (Kazimierz Wielki University, 2018)
Introduction and purpose of the work. Sedentary lifestyle being promoted at present is negatively affecting health and physical fitness of young people. Flat feet is a defect of lower limbs which consists in lowering arches shaping feet. The foot, under normal conditions, rests with three points on the ground: a calcaneal tuber, the head of the first and fifth metatarsals. The purpose of the work was to evaluate longitudinal and transverse arches of children from świętokrzyskie voivodship. Material and methods. The study involved 184 children from świętokrzyskie voivodship. The majority of the respondents were female - 100, whereas the male respondents - 84 people. The MS Excel program and the statistical program R.3.3.1 were applied therefor. The Clarke's angle index and the Wejsflog index were was used to assess the foot arch. The relationships between these parameters and gender, age, and BMI were investigated as well. Results. As a result of the conducted studies, the correct structure of both feet was found in 51% of the examined children. Flat feet of both feet was found in 4 children, whereas 34 children demonstrated a reduced arch of both feet. The problem of a reduced arch in one foot concerned 48 children, while 5 children had one foot with an elevated arch. Conclusions. Children with higher BMI index tend to have a decreased feet arch. With age, the Clarke's angle values decrease.